Integration of Islamic Education and General Education in Fazlur Rahman's Thoughts - Muhtadi Abdul Mun’im; Mamluatul Hasanah (LECTURES: Journal of Islamic and Education Studies, 2025)
This study examines the thoughts of Islamic education by one of the reformers in the 20th century, namely Fazlur Rahman. This study aims to examine Fazlur Rahman's thoughts on Islamic Education and General Education. The main objective is to understand the concepts proposed by Fazlur Rahman in overcoming the dichotomy between religious knowledge and general knowledge, and how these concepts can inform educational practices in the context of increasingly advanced technology. This study is a library research where the main ideas of Fazlur Rahman's education are studied in this study. The main data sources are written works, articles, and books produced by Fazlur Rahman, as well as literature relevant to the issue of integrating Islamic education and general education. Data are analyzed through text analysis to identify concepts, themes, and ideas that emerge in Fazlur Rahman's thoughts. The results of the study reveal that Fazlur Rahman said that there must be integration between Islamic Education and General Education as a step towards a more comprehensive understanding of reality. Integration of Islamic Education and General Education can help overcome the dichotomy and promote a holistic understanding of the world. This study provides insight into how Fazlur Rahman's thoughts can provide guidance in developing relevant and inclusive education in today's era.